Carboplatin AUC 10 for IGCCCG good prognosis metastatic seminoma. (June 2013) - Tookman, Laura; Rashid, Sukaina; Matakidou, Athena; Phillips, Melissa; Wilson, Peter; Ansell, Wendy; Jamal-Hanjani, Mariam; Chowdhury, Simon; Harland, Stephen; Sarwar, Naveed; Oliver, Timothy; Powles, Thomas; et al.
Abstract Objective. Metastatic seminoma is a highly curable disease. Standard treatment comprises of combination chemotherapy. The short- and long-term toxicities of this treatment are increasingly recognised and the possibility of over treatment in such a curable disease should be considered. We have therefore assessed the use of single agent carboplatin at a dose of AUC 10 in patients with good prognosis metastatic seminoma. Materials and methods. Patients with good prognosis metastatic seminoma treated with carboplatin (AUC 10) were identified at our institution and affiliated institutions. Treatment was three weekly for a total of three or four cycles. Outcome and toxicities were analysed. Results. With a median follow-up of 36 months, 61 patients in total were treated with carboplatin AUC 10, all good prognosis by the IGCCCG criteria. Forty-eight percent had stage IIA/IIB disease and 52% had greater than stage IIB disease. Thirty-one patients (51%) had a complete response following treatment. Three-year survival was 96.3% with a three-year progression free survival of 93.2%. The main treatment toxicity was haematological with 46% having grade 3, 24% having grade 4 neutropenia and 54% experiencing grade 3/4 thrombocytopenia. There were no treatment related deaths. Conclusion. Single agent carboplatin at a dose of AUC 10 is an effective treatment for good prognosis metastatic seminoma. The outcome compares favourably to previously published outcomes of combination chemotherapy. Although haematological toxicity is a concern, single agent carboplatin treatment for good prognosis metastatic seminoma could be considered a treatment option and is associated with less toxicity than combination regimens currently used.